2014
DOI: 10.1007/s13187-014-0745-4
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Acceptability of Human Papillomavirus Vaccination and Cervical Cancer Screening among Women in Karnataka, India

Abstract: Cervical cancer is the leading cause of cancer-related mortality among women in India; however, participation in prevention and screening is low and the reasons for this are not well understood. In a cross-sectional survey in August 2008, 202 healthy women in Karnataka, India completed a questionnaire regarding knowledge, attitudes, and practices related to human papillomavirus (HPV) and cervical cancer. Factors associated with vaccination and Papanicolau (Pap) smear screening acceptance were explored. Thirty-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
66
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(74 citation statements)
references
References 26 publications
5
66
3
Order By: Relevance
“…Various studies have shown a very poor level of awareness regarding the HPV vaccine. 11,13,14 For the public to be aware, it is essential that those in the medical field have a sound knowledge first. This includes health care professionals as well as medical students.…”
Section: 12mentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies have shown a very poor level of awareness regarding the HPV vaccine. 11,13,14 For the public to be aware, it is essential that those in the medical field have a sound knowledge first. This includes health care professionals as well as medical students.…”
Section: 12mentioning
confidence: 99%
“…There are a number of reasons for this, main reasons being lack of awareness-about the relationship of HPV with cervical cancer and about the availability of the vaccine, high costs and recent unproved controversies stating that these vaccines have had adverse side effects. 11 This lack of awareness is a matter of concern as one of the ways by which we can decrease the burden of cervical cancer is by mass vaccination against HPV and mass screening programs.…”
mentioning
confidence: 99%
“…Researchers found that the knowledge of 202 healthy Indian women relating HPV to CC was low because they did not know the most coherent method to prevent CC (Montgomery, Dune, Shetty, & Shetty, 2015). This confirms that low knowledge about HPV is associated with less ability to correctly prevent this oncogenic agent by performing the Pap smear screening test.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, 77 papers and one dissertation were eligible for analysis and were listed in the order of publication years. [171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273747576777879808182838485868788899091929394] The review process is explained in Figure 1.…”
Section: Methodsmentioning
confidence: 99%